Midregional proadrenomedullin predicts reduced blood pressure and glucose elevation over time despite enhanced progression of obesity markers. Issue 3 (March 2019) - Ohlsson, Therese; Nilsson, Peter M.; Persson, Margaretha; Melander, Olle
Abstract : Objectives: Elevated plasma levels of the vasodilating hormone adrenomedullin (ADM) predict cardiovascular disease and have been associated with hypertension and obesity. We aimed to examine the independent relationship between ADM and the progression of major cardiometabolic risk factors during long-term follow-up. Methods: We studied midregional pro-ADM (MR-proADM) in fasting plasma in 3298 participants from the population-based Malmö Diet and Cancer Study – Cardiovascular Cohort, re-examined after 17 years of follow-up and related baseline MR-proADM to cardiometabolic risk factors cross-sectionally and longitudinally. Results: At baseline, after full adjustment, each SD increment of MR-proADM was independently related to (beta ± standard error, P value) higher SBP (0.956 ± 0.319 mmHg, P = 0.003), BMI (0.912 ± 0.061 kg/m 2, P = 1.42 × 10 −48 ), waist (2.28 ± 0.158 cm, P = 8.46 × 10 −46 ) and fasting blood glucose (0.046 ± 0.018 mmol/l, P = 0.01). After full adjustment, including the baseline level of the risk factor whose degree of progression was studied, each SD increment of MR-proADM predicted significantly reduced progression of SBP (−1.170 ± 0.337 mmHg, P = 0.001) and fasting blood glucose (−0.055 ± 0.023 mmol/l, P = 0.015), but greater increase of BMI (0.101 ± 0.051 kg/m 2, P = 0.047) and waist (0.600 ± 0.144 cm, P = 3.1 × 10 −5 ). Conclusion: Despite cross-sectional associations with higher levels of blood pressure and glucose, high levels of MR-proADM predict a slower progression of blood pressure and glycemia during long-term follow-up. Conversely, the cross-sectional associations with higher levels of MR-proADM and obesity were paralleled by a faster progression of obesity markers over time. These results may be important for assessment of long-term effects of therapies modulating levels of ADM.